2006
DOI: 10.1002/chem.200501113
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐Substituted 1,1,4,4‐Tetracyanobutadienes (TCBDs): New Chromophores with Efficient Intramolecular Charge‐Transfer Interactions by Atom‐Economic Synthesis

Abstract: A wide variety of monomeric and oligomeric, donor-substituted 1,1,4,4-tetracyanobutadienes (TCBDs) have been synthesized by [2+2] cycloaddition between tetracyanoethylene (TNCE) and donor-substituted alkynes, followed by electrocyclic ring opening of the initially formed cyclobutenes. Reaction yields are often nearly quantitative but can be affected by the electron-donating power and steric demands of the alkyne substituents. The intramolecular charge-transfer (CT) interactions between the donor and TCBD accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
228
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 268 publications
(263 citation statements)
references
References 77 publications
25
228
0
7
Order By: Relevance
“…A distinct solvatochromic effect of (TCNQ) 2 OPV 3 has been observed in varied solvents, which was a characteristic behavior of the dipolar ICT molecules. [19][20][21][22]44 The major CT band at 677 nm (1.83 eV) in CH 2 Cl 2 red-shis to 687 nm (1.80 eV) in CH 3 CN and 718 nm (1.73 eV) in DMF, and blue-shis to 658 nm (1.88 eV) in THF and 625 nm (1.98 eV) in toluene. The solvent effect of the CT band generally follows the reported tendency of red shi of such ICT compounds when increasing the solvent …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A distinct solvatochromic effect of (TCNQ) 2 OPV 3 has been observed in varied solvents, which was a characteristic behavior of the dipolar ICT molecules. [19][20][21][22]44 The major CT band at 677 nm (1.83 eV) in CH 2 Cl 2 red-shis to 687 nm (1.80 eV) in CH 3 CN and 718 nm (1.73 eV) in DMF, and blue-shis to 658 nm (1.88 eV) in THF and 625 nm (1.98 eV) in toluene. The solvent effect of the CT band generally follows the reported tendency of red shi of such ICT compounds when increasing the solvent …”
mentioning
confidence: 99%
“…These naturally stable, nonplanar chromophores are ideal platforms for efficient intramolecular charge-transfer (ICT) processes and are regarded as promising nonlinear optical materials. [19][20][21][22][32][33][34][35][36] In this work, we have designed and synthesized an oligo-(phenylenevinylene) (OPV) bridged ICT compound, (TCNQ) 2 -OPV 3 , and studied its third-and h-order optical nonlinearities by a nonlinear optical imaging technique with the phase-object (NIT-PO) at the entry of a 4f coherent imaging system. 37 The method is based on a 4f system with top-hat beams and its theoretical model is simple Fourier optics, which leads to many advantages such as simple optical alignment, very high sensitivity and insensitivity to statistical uc-tuations of the laser beam.…”
mentioning
confidence: 99%
“…Diederich and his co-workers systematically investigated the reactivity of alkyne molecules, and they found that aromatic amines, such as N,N-dialkylaniline, are some of the best substituents for the effective activation of the alkyne moiety. 45 It was found by later studies that other donors, such as thiophene, tetrathiafulvalene (TTF), porphyrin, azulene, and some organometallic substances, are also effective for the activation of the alkyne moiety (see Figure 16). 4653 Moreover, several TCNQ and other quinodimethane derivatives, such as 2,3,5,6-tetrafluoro-TCNQ (F 4 -TCNQ), 2,5-dialkoxy-TCNQ, and 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ), can also be employed as effective acceptors of these reactions (see Figure 16).…”
Section: Chemosensors Based On New "Alkyne-acceptor" Click Reactionsmentioning
confidence: 99%
“…9), accessible in often quantitative yields in an atom-economic synthesis [85] by formal [2+2] cycloaddition between TCNE and donor-substituted alkynes, followed by electrocyclic ring-opening of the initially formed cyclobutenes [86,87]. The [2+2] cycloaddition of TCNE with electron-rich metal acetylides, followed by retro-electrocyclization to give organometallic TCBD derivatives had actually been described by Bruce and coworkers as early as 1981 [88,89], but the corresponding reaction with electron-rich alkynes had not been systematically explored [90,91].…”
Section: Donor-substituted 1144-tetracyanobuta-13-dienes: Charge-mentioning
confidence: 99%
“…10) are particularly remarkable. Thus, the trimeric derivative 27 undergoes six reversible one-electron reduction steps, each centered on a dicyanovinyl moiety, in the narrow potential range between -0.69 and -1.69 V [87] (Fig. 10).…”
Section: Donor-substituted 1144-tetracyanobuta-13-dienes: Charge-mentioning
confidence: 99%